SOCIAL MEDIA ANALYSIS AND PRODUCT QUALITY ON CONSUMER BEHAVIOR IN PURCHASING DECISIONS ON TIKTOK E-COMMERCE - Sifak, Devi Afifatus; Hakim, Lukman (International Conference on Humanity Education and Society (ICHES), 2024)
This study aims to analyze how the influence of Social Media and Product Quality on purchasing decisions on TikTok E-Commerce. Considering that TikTok Social Media after being closed and reopened at this time can be used as a consideration by business people in running their business on TikTok Social Media, whether TikTok social media after reopening is still effective as a digital marketing platform, and whether people also still have the desire to make purchase decisions on TikTok Social Media. This study used a quantitative approach with a sample number of 100 respondents. The sampling method in this study uses non-probability sampling with purposive sampling techniques. Data management techniques in this study use Statistical Package for the Social Sciences (SPSS) software with data collection techniques using google form which will then be given to respondents then respondents can fill in answers to questions given according to what happened. The results of this study show that social media and product quality have a positive and significant influence on purchasing decisions. This means that marketing on social media is considered quite effective , the reason why TikTok can be used as a marketing platform is proven by the large number of users and there is a TikTok Shop feature with the support of interesting content, as well as customer reviews that can show the quality of the product is able to make customers consider buying according to their needs.